Dream Shot : The Journey to a Wheelchair Basketball National Championship - Birnbaum, Josh, 1985- (Book collections on Project MUSE., 2017)
"Uphill Battle is primarily a photography book documenting the 2007-2008 University of Illinois men's wheelchair basketball team which won the 2008 national championship. The author traveled with the team and took 45,000 photographs from which he will select 100 images for this book. The images and accompanying captions will show what it's like to be disabled and an athlete, but also to show commonality amongst human beings, to foster understanding more than emphasize difference. One of the players on the championship team is now the coach of the current Illini wheelchair team. He will write an introduction that will cover the inception of the Illinois wheelchair basketball program, his perspective as player and coach, anecdotes from the season, and the lasting impact of the championship. The book will also include "where are they now" profiles of each player on the 2007-2008 team and a current photo"--